Effects of adding NSP enzymes to barley-based diets on carcass composition and digestive function of piglets - YU Song-dong; LI Wei-fen; SUN Jiang-yi; XU Zi-rong (浙江大学学报. 农业与生命科学版, 2002)
Sixty piglets (Duroc × Yorkshire × Jia) were used to study the effects of NSP enzymes (including β-glucanase, xylanase and cellulase) added to barley-based diets on digestive function of piglets. The results showed that compared to control group, NSP enzymes increased the content of glucose and bile acid in small intestinal digesta by 48.91% (P<0.01) and 73.50% (P<0.01), decreased the viscosity by 6.31% (P<0.05); increased the height of villi and microvilli by 50.00% (P<0.01) and 55.91% (P<0.01), decreased the depth of mucosa layer by 72.00% (P<0.01), the number of E. coli. in feces and diarrhea morbidity by 69.8% and 62.59% (P<0.05), respectively.